Service Ecosystem Design: Propositions, Process Model, and Future Research Agenda - Vink, Josina; Koskela-Huotari, Kaisa; Tronvoll, Bård; Edvardsson, Bo; Wetter-Edman, Katarina (Journal of service research : JSR, 2021)
While service design has been highlighted as a promising approach for driving innovation, there are often struggles in realizing lasting change in practice. The issues with long-term implementation reveal a reductionist view of service design that ignores the institutional arrangements and other interdependencies that influence design efforts within multi-actor service systems. The purpose of this article is to build a systemic understanding of service design to inform actors’ efforts aimed at intentional, long-term change in service systems. To achieve this aim, we inform the conceptual building blocks of service design by applying service-dominant logic’s service ecosystems perspective. Through this process, we develop four core propositions and a multilevel process model of service ecosystem design. The conceptualization of service ecosystem design advances service design theory by illuminating previously taken for granted aspects; explaining how intentional, long-term change emerges; and expanding the scope of service design beyond projects. Furthermore, this research offers a foundation for future research on service design that involves extending the systemic conceptualization of service design, conducting more holistic empirical investigations, and developing practical methods and approaches for the embedded, collective processes of designing.